Assessing the possibility of using wind energy in the East-South-Eastern part of Turkmenistan - Kochayeva Akjagul; Amanakov Annameret; Muradova Sulgun; Suleymanov Resul; Atayeva Ayna (E3S Web of Conferences)
The paper considers the assessment of the energy potential of wind energy in the eastern part of Turkmenistan, namely for the Koytendag district, various combinations of wind power plants are considered. It was determined that the installation of two wind power plants with a capacity of 0.75 MW does not cover the consumption of electricity. It was revealed that the minimum deficit is observed in February (12.6%), and the maximum in September (78.6%). It was analyzed that only in January there is an excess (12%). It was revealed that the installation of two wind power plants with a capacity of 1.5 MW gives an excess of 40% in December to 134% in March of energy consumed. The calculations made for the city of Atamurat considered various combinations of wind power plants, and as a result it was found that the installation of two wind power plants with a capacity of 0.75 MW each also does not cover consumption. It was found that for this case the minimum deficit is observed in July (16.5%), and the maximum in September (77.2%), and the maximum in January (2%) and March (17%). It was determined that the installation of two wind power plants with a capacity of 1.5 MW provides from 48.9% in August to 149.4% in March of the consumed amount. It is proposed as the optimal option for both regions to install one wind power plant with a capacity of 0.75 MW and one 1.5 MW with an output voltage of 690 V.